Working Hard for the Ones You Love and Care for Under Covid-19 Physical Distancing. (December 2021) - Vermeerbergen, Lander; Pulignano, Valeria; Domecka, Markieta; Jansens, Marieke
In 2020, Covid-19 was spreading quickly in nursing homes, leading to numerous challenges for care workers. We tell the story of Marieke, a devoted female care assistant working in a Belgian nursing home that is customer-centred in their organisational model. Her narrative provides poignant insights into the 'work and life' struggles and conflicts of a female care assistant facing the challenges of this model during the Covid-19 pandemic, which has left the largely female care workforce widely exposed to the risk of work intensification and over-involvement with residents, especially in a context of liberalisation and privatisation of care. In the early stages of the Covid-19 pandemic, this model led to Marieke facing the unprecedented fear of endangering her own life and the lives of those she loves. In this article, she reflects on her work and family life under the strain of ensuring physical distancing in a nursing home.